Do the regulations for street music in Spain lead urban musicians to break the law? - Ospina Gallego, Crismary; Lloret Romero, Maria Nuria; Betancur Santa, Héctor Yovanny (Street Art & Urban Creativity, 2024)
Do the regulations for street music in Spain lead urban musicians to break the law? This study focuses on street musicians who sing or play musical instruments in a public space for donations/tips. Currently most of their needs are not covered in the laws relating to of street musicians in Spain, several cities do not have this profession regulated and in the localities that do, they prohibit amplification, the sale of their own music (CDs etc.), limit free movement and the instruments that they can use. These are rules that musicians must break in order to work, leaving the buskers who perform in a legal gap or limbo, without defense against the authorities. This study addresses 3 parts: the first is an observational exercise from the perspective of the street musician which seeks to find out the basic needs of workers in their busking experience; the second area analyzes how the Spanish regulations behave based on the needs that these performers have; and the third element contrasts the personal view of the researcher with the opinions of other street musicians and groups found in the media.